Entre razón y ciencia de la Hacienda: la conflictiva construcción de un modelo de buen gobierno de la Real Hacienda en España en la primera mitad del siglo XVIII - Dubet, Anne (Espacio Tiempo y Forma. Serie IV, Historia Moderna, 2015)
¿Existe o no un saber específico en materia de Hacienda, e incluso una ciencia? ¿Este saber justifica el acceso al poder o el monopolio del poder en materia de Hacienda? El examen del debate que se da en España en torno a estas cuestiones durante los reinados de Felipe V y Fernando VI permite acercarse a las concepciones del buen gobierno de la Hacienda de los actores. Asimismo, da cuenta de la existencia de unos enfrentamientos políticos que no se pueden reducir a la oposición usual entre un reformismo borbónico, supuestamente homogéneo, y la tradición austracista. La construcción de un nuevo modelo de gobierno de la Hacienda fue conflictiva y sinuosa. The Spanish actors in Eighteenth Century discussed about two related questions. First, the extent to which there existed in Spain a specific knowledge, or even a specific science, of finance administration. Second, they asked whether this knowledge was a justification for exercising power over the administration of finance. The paper explores the polemics that these two questions raised, under the reigns of Philip V and Ferdinand VI. Our aim is to reconstruct and understand the conceptions of good financial administration according to its key actors. Our conclusions show that the political confrontations in this period should not be read as the result of a traditional conflict opposing Bourbon’s reformism (supposedly homogeneous) and pro-Habsburg tradition. In fact, the construction of a new model of financial administration was a conflicting and far from straightforward issue.